Mengasah Kreativitas Siswa Sekolah Dasar Melalui Kegiatan Ecoprint Desa Kedungsuren - Aden PaiqMuntaz; Muhammad Ilham Prasetya; Irgi M. Aqil Daeng Masiga; Eko Setyo Nugroho; Muhammad Zacky Sulthoni; Nabila Mey Nur Hardini; Fatimah Nisa Royyani; Dwi Ayu Novita; Nur Hijratun Nafiah; Itsna Cholifatun Nisa; Nadya Sya’ada; Anisa Badriyah; Avika Fitriana Assari; Shovi Zaidatul Ma’rifah; Aulia Najwa Zaen; Najichah M.H (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
This research aims to improve the creativity of elementary school students through ecoprint activities at SD 03 Kedungsuren and MI NU 58 Kedungsuren, Kaliwugu Selatan. The method used is Participatory Action Research (PAR) method. This research involved fourth grade students and was conducted through the stages of planning, action, observation, and reflection in a collaborative manner. This PAR method allows active involvement of students and teachers in learning to create a participatory and reflective environment. The results of this research show an increase in students' creativity in imagination, innovation, technical skills, as well as cooperation skills and appreciation of the environment. The findings provide positive implications for the development of environment-based creative learning methods, which can be used as a reference for other schools.